2020
DOI: 10.1002/brb3.1492
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among variants in P53 apoptotic pathway genes are associated with neurologic deterioration and functional outcome after acute ischemic stroke

Abstract: Objective: Neurologic deterioration (ND) and functional outcome after ischemic stroke (IS) are not accurately predicted by clinical pictures on admission. The aim of present study was to investigate the association of variants in P53 apoptotic pathway genes with ND and functional outcome after IS.Methods: Genotypes of nine variants in apoptosis-relevant genes were measured in patients with acute IS. Gene-gene interactions were analyzed by generalized multifactor dimensionality reduction (GMDR). The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Fourth, some studies showed that the standard-reaching rate for hypertension, diabetes mellitus, and dyslipidemia (embodied in blood pressure, glucose, and lipids) was very low, and was associated with outcomes ( 10 , 11 ). However, some studies thought that blood pressure, blood glucose, and lipids, as the intermediate markers during medication treatment, were not associated with susceptibility to stroke and outcomes ( 33 , 34 ). In this study, although we investigated the persistence of antihypertensives, hypoglycemics, lipid-lowering medications, and antithrombotics in the high-risk stroke population, the relevant data such as blood pressure, glucose, and lipids at 4.7 years after a face-to-face survey were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, some studies showed that the standard-reaching rate for hypertension, diabetes mellitus, and dyslipidemia (embodied in blood pressure, glucose, and lipids) was very low, and was associated with outcomes ( 10 , 11 ). However, some studies thought that blood pressure, blood glucose, and lipids, as the intermediate markers during medication treatment, were not associated with susceptibility to stroke and outcomes ( 33 , 34 ). In this study, although we investigated the persistence of antihypertensives, hypoglycemics, lipid-lowering medications, and antithrombotics in the high-risk stroke population, the relevant data such as blood pressure, glucose, and lipids at 4.7 years after a face-to-face survey were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset contains the raw data (supplementary Table), frequencies of alleles and genotypes ( Table 1 ) for three SNPs of two MMP genes (rs1799750 MMP1 , rs3918242 and rs17576 MMP9 ) in Russian patients diagnosed with POAG, EH, and PU. These polymorphisms were previously reported for their association with POAG, EH, and PU ( Table 2 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . The studied SNPs manifest the regulatory potential ( Table 3 ), which is evidenced by several eQTLs ( Table 4 ) and splicing QTLs ( Table 5 ).…”
Section: Data Descriptionmentioning
confidence: 85%
“…p53-mediated neuronal apoptosis plays vital role on stroke pathophysiology and ischemic penumbra injury.Until now,two studies has investigate the p53 apoptotic pathway related gene (P53, P21, MDM-2, and MMP-9 )with functional outcome after IS. Cristina et al has rst found that MDM2 rs2279744 G allele had increased MDM2 protein expression and was associated with better functional outcome after stroke [21]. Their results revealed that MDM2 rs2279744 determines the functional outcome of patients after stroke through regulating the MDM2-p53 interaction.Subsequently, a study by Yi et al identi ed that interactions among P53 rs1042522, MDM-2 rs2279744, and MMP-9 rs3918242 may jointly increase the risk of poor functional outcome and may be biomarker of predicting poor functional outcome after stroke [22].However, the role of p53 apoptotic pathway related LncRNA genes polymorphism and IS prognosis has not been thoroughly understood.…”
Section: Discussionmentioning
confidence: 98%